ĀTMAVAT SARVBHŪTEṢU THE SPIRITUAL PATHWAY TO SOCIAL HARMONY - Bhatt, Chirag Niranjan; Trivedi, Rajeshri (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The foundation of a good life lies in the quality of our social relationships. The teachings of His Divine Holiness Hariprasad Swamiji Maharaj led a socio-spiritual revolution of Atmiyata. The research elaborates on the profound impact of spiritual harmony on social relationships. Complementing these spiritual insights, the findings of the 75-year-long Harvard Study of Adult Development reveal that the quality of our social connections significantly influences happiness, health, and longevity. This paper explores the synergy between these two perspectives, highlighting how spiritual principles, such as self-control and detachment as described in the Bhagavad Gita, enhance social bonds and personal well-being. By integrating Swamiji's teachings with modern scientific insights, the paper advocates for a balanced life approach that nurtures both spiritual growth and healthy social relationships, ultimately leading to holistic happiness and societal harmony